Spatial Patterns of Larval and Juvenile Fish Assemblages in an Eddy Area in the Western South China Sea - Wu, ChenYan; Wang, XiaoGu; Zhong, JunSheng; Ju, JiaLi; Li, ChenHong (Frontiers in Marine Science, 2022)
The objective of this study was to investigate influence of meso-scale eddies in the western South China Sea on species composition and spatial patterns of fish larvae and juveniles based on the data collected during summer and autumn in 2012. Nintyeight species belonging to 38 families were collected, including 78 species in summer and 41 species in autumn. The dominant species in summer were Vinciguerria sp. (39.70%), Stephanolepis cirrhifer (11.21%), Caranx sp. (5.45%) and Benthosema pterotum (1.97%). The dominant species in autumn were Gobiidae sp. (15.32%), Ceratoscopelus townsendi (7.26%), Diaphus sp. (6.45%), Astronesthes sp. (5.65%) and Callionymidae sp. (4.03%). Abundance of fish larvae and juveniles in summer was higher than that found in autumn. Similarity cluster analysis results indicated that larval fish assemblages in summer can be divided into two communities: (1) larval fish in the cyclonic eddy; (2) larval fish in the anticyclonic eddies. While in autumn, the larval fish assemblages can be divided into three communities: (1) larval fish without influence of the cyclonic eddy; (2) larval fish influenced slightly by the cyclonic eddy; (3) larval fish gathered near the center of the cyclonic eddy. The variations of abundance and assemblage of larval fish might be attributed to sea surface temperature (SST), sea surface salinity (SSS) and sea level anomaly (SLA).